Lilliputian Neglected Happenings Call For Snafu: “Theory of Broken Windows” (Medico Legal Update, 2020)
This article named “Lilliputian neglected happenings call for snafu” is a work focusing on the small things that are usually neglected and avoided during policing which further leads to hampering of peace and harmony in the neglected society or community thus giving a chance to the delinquents and offenders to foul up and create a chaotic situation. This work is inspired from the “Theory of Broken Windows” which was introduced by James Q Wilson and George L. Kelling in March 1982 in an article named “Broken Windows: The Police & neighborhood safety” in The Atlantic, retrieved 2007-09-03. This article first starts explaining the definition and origin of theory in general then how it reached its targeted audience and got popularized. The influencing power of the theory has been elaborately discussed, its theoretical tendency to revamp the policing methods have been stated and then the practical adoption of the theory by the New York police department and the consequences of the same have been enunciated. Finally the observation after through research works whether the theory is practically persistent or not has been deduced along with the concluding remarks.